Quality of life among peri menopausal and post-menopausal women from rural area of Western India - Maniktalla, Sanjana; Gothankar, Jayashree Sachin; Narula, Arvinder Pal Singh (International Journal of Public Health Science (IJPHS), 2025)
Menopause, remains a poorly investigated topic holding increased taboo. In addition to symptoms categorized under vasomotor, vaginal, energy, food and insomnia, it is linked to occurrence of various medical comorbidities. Understanding the status of menopause symptoms and awareness will help provide insight on how it influences women’s quality of life. Objective was to assess the association of menopause on attributes of sleep, energy, memory, work, leisure and everyday activities affecting quality of life. This was a community based cross-sectional study conducted over three months in randomly selected villages under rural field practice area of private medical college in Maharashtra. Data was collected during health camps along with house visits. Research tool containing socio-demographic, menopausal status and quality of life components was used targeting women aged 40-65 years. Logistic regression analysis was used to find odds ratio and adjusted odds ratio respectively for menopausal symptoms with associated attributes at 5% level of significance and 95% CI. Results showed the mean age of women was 48.16 years ±8.4 SD, by which 57% had fully attained menopause and it was associated with significant changes in sleep, memory and physical relations. This study lays emphasis on the fact that menopause period is associated with sleep and memory disturbances as well as physical relations in rural women. It also highlights on the poor knowledge and attitude pertaining to menopause in a rural setup.